2014
DOI: 10.1073/pnas.1411346111
|View full text |Cite
|
Sign up to set email alerts
|

Recent mountain pine beetle outbreaks, wildfire severity, and postfire tree regeneration in the US Northern Rockies

Abstract: Widespread tree mortality caused by outbreaks of native bark beetles (Circulionidae: Scolytinae) in recent decades has raised concern among scientists and forest managers about whether beetle outbreaks fuel more ecologically severe forest fires and impair postfire resilience. To investigate this question, we collected extensive field data following multiple fires that burned subalpine forests in 2011 throughout the Northern Rocky Mountains across a spectrum of prefire beetle outbreak severity, primarily from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
123
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 53 publications
11
123
3
Order By: Relevance
“…The increase in fire severity and synergism predicted in our study for red-phase stands under low-to moderate-wind speeds appears to contradict the conclusion by Harvey et al (2014a) that fire severity in lodgepole pine stands was largely unaffected by pre-fire bark beetle-outbreak severity. The differences between the two studies could be because Harvey et al studied a mid-red-phase lodgepole pine forest, with only ~50 % of the dead needles retained in the canopy, and our study addressed the early red phase, before any of the dead needles had fallen off the trees.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The increase in fire severity and synergism predicted in our study for red-phase stands under low-to moderate-wind speeds appears to contradict the conclusion by Harvey et al (2014a) that fire severity in lodgepole pine stands was largely unaffected by pre-fire bark beetle-outbreak severity. The differences between the two studies could be because Harvey et al studied a mid-red-phase lodgepole pine forest, with only ~50 % of the dead needles retained in the canopy, and our study addressed the early red phase, before any of the dead needles had fallen off the trees.…”
Section: Discussioncontrasting
confidence: 99%
“…The differences between the two studies could be because Harvey et al studied a mid-red-phase lodgepole pine forest, with only ~50 % of the dead needles retained in the canopy, and our study addressed the early red phase, before any of the dead needles had fallen off the trees. In addition, Harvey et al (2014a) studied mountain pine beetle-caused mortality that resulted in needle loss over multiple years, whereas the abrupt and widespread mortality that we studied in Southwestern ponderosa pine forests was incited by a "global change-type drought" (Breshears et al 2009) that increased susceptibility to multiple Ips and Dendroctonus bark beetle species, killing trees within one to two years (Negrón et al 2009). Finally, if the "moderate" and "extreme" burning conditions approximated by Harvey et al (2014a) by relative humidity and temperature also included higher wind speeds, their results are in line with our simulations that suggested that increasing levels of mortality during the red phase under moderate-and high-wind speeds led to minor and sometimes non-significant increases in fire severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impacts of this colossal outbreak, coupled (compounded) with large-scale salvage operations will likely lead to conditions outside the natural range of disturbances that these ecosystems have experienced historically [14,31,33]. Information regarding the response of pine-dominated ecosystems to disturbances such as fire and harvesting is available [2,[34][35][36]; however, it is still unclear whether stand dynamics will respond similarly with respect to a large-scale beetle epidemic. Therefore, understanding how MPB-attacked stands will develop and characterize the future landscape is essential for assessing the impending impacts on ecological and socioeconomic conditions.…”
Section: Introductionmentioning
confidence: 99%